Distribution of duck broods relative to habitat characteristics in the Prairie Pothole Region1. Issue 2 (8th October 2012) - Walker, Johann; Rotella, Jay J.; Schmidt, Joshua H.; Loesch, Charles R.; Reynolds, Ronald E.; Lindberg, Mark S.; Ringelman, James K.; Stephens, Scott E.
Abstract Conservation programs for breeding ducks in the Prairie Pothole Region (PPR) of the United States and Canada require effective means of evaluating and characterizing breeding habitat across large landscapes. Extensive surveys of the distribution of duck broods in late‐summer could help identify wetland basins with greater probabilities of occupancy. Broods are difficult to detect, however, rendering presence–absence data from single‐visit surveys difficult to interpret, particularly when probability of detection is related to habitat features. Multiple‐visit occupancy surveys offer a potential solution. From 20 July to 5 August 2007–2009, we conducted a 3‐visit survey of wetland basins located on 167 10.4‐km2 study plots in the PPR. Our survey focused on broods of the 5 most common breeding duck species (Anas spp.). Our main objectives were to investigate ecological relationships between occupancy of wetland basins by broods and habitat characteristics and to examine if habitat‐specific detection was of enough concern to warrant multi‐survey approaches in the future. We surveyed 3, 226 wetland basins during the study. Probability of occupancy of a wetland basin by a brood was positively related to the log of wet area for all 5 study species and was greater on wetlands located on plots with a greater proportion of herbaceous perennial cover for 4 of 5 species. For example, the median probability of occupancy for gadwall (Anas strepera) increased from 0.08 (90% Credible Interval [CrI]: 0.07, 0.10) to 0.28 (90% CrI: 0.23, 0.33) as wet area increased from 0.19 ha to 2.12 ha, and increased from 0.12 (90% CrI: 0.09, 0.16) to 0.20 (90% CrI: 0.16, 0.25) as proportion of perennial grass cover on the study plot increased from 0.03 to 0.99. Because occupancy and detection were both related to attributes of wetland basins, we concluded that the multiple‐visit survey was a useful approach for identifying habitat relationships of duck broods. Our results indicated that most broods of the study species were found in 10.4‐km2 landscapes with greater densities of small‐ to mid‐sized wetland basins and a greater proportion of herbaceous perennial vegetation. Our study provided new empirical support that could be used to help target conservation actions to the most productive landscapes for breeding ducks. © 2012 The Wildlife Society.